Supervised treatment in outpatients for schizophrenia plus (STOPS+): protocol for a cluster randomised trial of a community-based intervention to improve treatment adherence and reduce the treatment gap for schizophrenia in Pakistan - Christian Mallen; Zia Ul-Haq; Atif Rahman; Martyn Lewis; Thomas Andrew Shepherd; Mian Ul-Haq; Muhammad Firaz Khan; Adil Afridi; Michelle E Robinson; Umaima Saeed; Naila Riaz Awan (BMJ Open, 2020)
Introduction There is a significant treatment gap, with only a few community-based services for people with schizophrenia in low-income and middle-income countries. Poor treatment adherence in schizophrenia is associated with poorer health outcomes, suicide attempts and death. We previously reported the effectiveness of supervised treatment in outpatients for schizophrenia (STOPS) for improving treatment adherence in patients with schizophrenia. However, STOPS was evaluated in a tertiary care setting with no primary care involvement, limiting its generalisability to the wider at-risk population. We aim to evaluate the effectiveness of STOPS+ in scaling up the primary care treatment of schizophrenia to a real-world setting.Methods and analysis The effectiveness of the STOPS+ intervention in improving the level of functioning and medication adherence in patients with schizophrenia in Pakistan will be evaluated using a cluster randomised controlled trial design. We aim to recruit 526 participants from 24 primary healthcare centres randomly allocated in 1:1 ratio to STOPS+ intervention and enhanced treatment as usual arms. Participants will be followed-up for 12 months postrecruitment. The sample size is estimated for two outcomes (1) the primary clinical outcome is level of functioning, measured using the Global Assessment of Functioning scale and (2) the primary process outcome is adherence to treatment regimen measured using a validated measure. An intention-to-treat approach will be used for the primary analysis.Ethics and dissemination Ethical approval has been obtained from Keele University Ethical Review Panel (ref: MH-190017) and Khyber Medical University Ethical Review Board (ref: DIR-KMU-EB/ST/000648). The results of the STOPS+ trial will be reported in peer-reviewed journals and academic conferences and disseminated to local stakeholders and policymakers.Trial registration number ISRCTN93243890.